Molecular Electrostatic Potential and Noncovalent Interactions in Derivatives of Group 8 Elements. Issue 38 (16th August 2021) - Daolio, Andrea; Pizzi, Andrea; Calabrese, Miriam; Terraneo, Giancarlo; Bordignon, Simone; Frontera, Antonio; Resnati, Giuseppe
Abstract: This communication reports experimental and theoretical evidences of σ‐hole interactions in adducts between nitrogen or oxygen nucleophiles and tetroxides of osmium or other group 8 elements. Cocrystals between pyridine or pyridine N‐oxide derivatives and osmium tetroxide are characterized through various techniques and rationalized as σ‐hole interactions using DFT calculations and several other computational tools. We propose the term "osme bond" (OmB, Om=Fe, Ru, Os, (Hs)) for naming the noncovalent interactions wherein group 8 elements have the role of the electrophile. The word osme is the transcription of ὀσμή, the ancient Greek word for smell that was used to name the heaviest group 8 element in relation to the smoky odor of its tetroxide. Abstract : σ‐Hole interactions in adducts between nitrogen or oxygen nucleophiles and tetroxides of osmium or other group 8 elements are reported. Cocrystals between pyridine or pyridine N‐oxide derivatives and osmium tetroxide are characterized through various techniques including computational tools. We propose the term "osme bond" (OmB, Om=Fe, Ru, Os, (Hs)) for naming the noncovalent interactions wherein group 8 elements have the role of the electrophile.